Refining genome-wide associated loci for serum uric acid in individuals with African ancestry. (16th December 2019) - Chen, Guanjie; Shriner, Daniel; Doumatey, Ayo P; Zhou, Jie; Bentley, Amy R; Lei, Lin; Adeyemo, Adebowale; Rotimi, Charles N
Abstract: Objective: Serum uric acid is the end-product of purine metabolism and at high levels is a risk factor for several human diseases including gout and cardiovascular disease. Heritability estimates range from 0.32 to 0.63. Genome-wide association studies (GWAS) provide an unbiased approach to identify loci influencing serum uric acid. Here, we performed the first GWAS for serum uric acid in continental Africans, with replication in African Americans. Methods: Africans ( n = 4126) and African Americans ( n = 5007) were genotyped on high-density GWAS arrays. Efficient mixed model association, a variance component approach, was used to perform association testing for a total of 18 million autosomal genotyped and imputed variants. CAVIARBF was used to fine map significant regions. Results: We identified two genome-wide significant loci: 4p16.1 ( SLC2A9 ) and 11q13.1 ( SLC22A12 ). At SLC2A9, the most strongly associated SNP was rs7683856 ( P = 1.60 × 10 −44 ). Conditional analysis revealed a second signal indexed by rs6838021 ( P = 5.75 × 10 −17 ). Gene expression and regulatory motif data prioritized a single-candidate causal variant for each signal. At SLC22A12, the most strongly associated SNP was rs147647315 ( P = 6.65 × 10 −25 ). Conditional analysis and functional annotation prioritized the missense variant rs147647315 (R (Arg) > H (His)) as the sole causal variant. Functional annotation of these three signals implicated processes in skeletal muscle, subcutaneous adipose tissue and the kidneys, respectively. Conclusions: This first GWAS of serum uric acid in continental Africans identified three associations at two loci, SLC2A9 and SLC22A12 . The combination of weak linkage disequilibrium in Africans and functional annotation led to the identification of candidate causal SNPs for all three signals. Each candidate causal variant implicated a different cell type. Collectively, the three associations accounted for 4.3% of the variance of serum uric acid.